Transformation Of IAIN Into UIN And Internal Supervision Unit Model - Erwin Erwin; Nasfi Nasfi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
National Islamic Religious Universities (PTKIN) have begun to change their form, thus a supervisory step is needed in the form of an Internal Supervisory Unit (SPI) in accordance with the Regulation of the Minister of Religion of the Republic of Indonesia No. 25 of 2017. Where the PTKIN supervision system is required to focus on achieving Governance, control, risk management, but not just administrative activities. The steps and the presence of SPI in PTKIN are required by all elements to understand and share views on how the duties and responsibilities of SPI are, no less important is the leadership of PTKIN to the highest decision maker or top management. The research was conducted at 3 (three) PTKIN which will be transformed into a State Islamic University (UIN) using the